Macrolide Therapy in Chronic Inflammatory Diseases - Brygida Kwiatkowska; Maria Maślińska (Hindawi Limited, 2012)
Macrolides are a group of antibiotics with a distinctive macrocyclic lactone ring combined with sugars (cladinose, desosamine). The action of macrolides is to block protein synthesis by binding to the subunit of 50S ribosome of bacteria. Prototype macrolide was erythromycin, which came into clinical practice in the 50s of the 20th century. Its antimicrobial spectrum covers the scope of the penicillins but is extended to the impact of atypical bacteria. In the 90s more drugs of this group were synthesized-they have less severe side effects than erythromycin, extended spectrum of Gram-negative bacteria. Macrolides are effective in treating mycobacterial infections especially in patients infected with HIV. It is now known that in addition to antibacterial abilities, macrolides have immunomodulatory effects-they inhibit the production of proinflammatory cytokines (TNF, IL1, 6, and 8) affect transcription factors (NF-κB) as well as costimulaton (CD 80) and adhesion molecules (ICAM). This review article focused not only on the their antimicrobial abilities but also on efficacy in the treatment of several inflammatory disorders independent of the infectious agent. Their wider use as immunomodulators requires further study, which can lead to an extension of indications for their administration.